2020
DOI: 10.1080/21870764.2020.1750102
|View full text |Cite
|
Sign up to set email alerts
|

Structure and corrosion behavior of ZrN/CrN nano-multilayer coating deposited on AISI 304 stainless steel by CAE-PVD technique

Abstract: In this study, a zirconium nitride/chromium nitride nano-multilayer coating was deposited on AISI 304 specimen using cathodic arc evaporation-physical vapor deposition (CAE-PVD). The characterization of the samples were evaluated by scanning electron microscopy (SEM), field emission-SEM (FE-SEM), and X-ray diffraction (XRD). To evaluate effect of immersion time on the electrochemical behavior of ZrN/CrN nano-multilayer coating using electrochemical impedance spectroscopy (EIS) measurements were carried out in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The CPE impedance ( Z CPE ) is expressed as follows (Equation ()) 12,15 : ZCPEbadbreak=1Qjωn\begin{equation}{Z_{{\rm{CPE}}}} = \frac{1}{{Q{{\left( {j\omega } \right)}^n}}}\ \end{equation}where Q , j , ω , and n , respectively, are related to the CPE with unit of S α /(Ω cm 2 ), imaginary unit, the angular frequency with unit of rad/s, and surface uniformity coefficient. The parameters Q and n are independent of frequency 55 …”
Section: Resultsmentioning
confidence: 99%
“…The CPE impedance ( Z CPE ) is expressed as follows (Equation ()) 12,15 : ZCPEbadbreak=1Qjωn\begin{equation}{Z_{{\rm{CPE}}}} = \frac{1}{{Q{{\left( {j\omega } \right)}^n}}}\ \end{equation}where Q , j , ω , and n , respectively, are related to the CPE with unit of S α /(Ω cm 2 ), imaginary unit, the angular frequency with unit of rad/s, and surface uniformity coefficient. The parameters Q and n are independent of frequency 55 …”
Section: Resultsmentioning
confidence: 99%
“…The behavior of an ideal capacitor cannot be observed in the impedance data. So, CPE is used rather than the capacitor of the selected ECM 54–56 . The obtained data from the ECM is listed in Table 2 for all of the specimens after 48 h of immersion time.…”
Section: Resultsmentioning
confidence: 99%
“…Multilayer coatings have better performances, such as wear resistance and corrosion resistance, which could be widely used to improve the performance and service life of components in complex environments [9][10][11][12][13][14][15]. CrN single-layer coatings have the strongest hindrance to ion release [9], while CrN/TiN multilayer coatings have higher hardness and corrosion resistance [10].…”
Section: Introductionmentioning
confidence: 99%
“…The high density of CrN/TiN multilayer coatings also prevents the penetration of corrosive solutions into the substrate, thus improving the corrosion resistance [11,12]. In addition, Samim et al found that ZrN/CrN multilayer coatings have extremely high polarization resistance and different layers can act as a barrier to the penetration of corrosive solutions [13], and the absence of pits or any serious damage on their surfaces is due to the presence of an anti-corrosion barrier that prevents corrosion from occurring [14]. Vengesa et al reported that CrN/CrAlN multilayer coatings annealed at 700 • C had the highest corrosion resistance, which can be attributed to the presence of Cr 2 N as a corrosion-resistant phase [15].…”
Section: Introductionmentioning
confidence: 99%